PENGARUH LDR DAN LAR TERHADAP NPL PADA BPR DI KOTA SEMARANG DENGAN CAR DAN BANK SIZE SEBAGAI VARIABEL KONTROL (STUDI KASUS PADA OJK PERIODE 2016-2020) - Choiriyah, Siti; Lisiantara, G. Anggana (2021)
This study aims to examine the effect of LDR and LAR on NPL on Rural Bank in Semarang City with CAR and Bank Size as control variables in the Financial Services Authority for 2016-2020 periods. The sampling method used is saturated sampling (population census), which is a sampling technique that takes all members of the population as a samples. The population used in this research was 24 BPR. The analytical tool used is multiple linear regression analysis. The results indicated that LDR had significant positive effect on NPL, LAR had a significant negative effect on NPL, and the control variables CAR and bank size had no significant effect on NPL.